1997
DOI: 10.1038/bjc.1997.175
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative response of human and animal tumours to surgical wounding of normal tissues: onset, duration and inhibition

Abstract: Summary Acceleration of secondary tumour growth and metastases following excision of a primary tumour has been attributed to the consequent removal of primary tumour-generated inhibitory factors. However, our studies have shown that surgical wounding of normal tissues significantly stimulated the growth of malignant tissues without the concomitant presence or excision of a tumour mass. A humoral stimulating component was indicated by the proliferative response of tumours and metastases distant from the surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 10 publications
1
48
0
1
Order By: Relevance
“…Various other mechanisms explain how other factors like VEGF, PDGF and interleukins influence tumour growth (Dvorak, 1986;Dvorak et al, 1995;Abramovich et al, 1999;Balkwill and Mantovani, 2001;Coussens and Werb, 2002;Chang et al, 2005). There is also evidence to suggest that cell-mediated immunity and natural killer cell function is suppressed by the effect of anaesthesia and the post-surgical stress response (Bogden et al, 1997). If this 'window period' of decreased immunity is prolonged by wound complications like flap necrosis and breakdown, there may be increased growth of occult micro metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Various other mechanisms explain how other factors like VEGF, PDGF and interleukins influence tumour growth (Dvorak, 1986;Dvorak et al, 1995;Abramovich et al, 1999;Balkwill and Mantovani, 2001;Coussens and Werb, 2002;Chang et al, 2005). There is also evidence to suggest that cell-mediated immunity and natural killer cell function is suppressed by the effect of anaesthesia and the post-surgical stress response (Bogden et al, 1997). If this 'window period' of decreased immunity is prolonged by wound complications like flap necrosis and breakdown, there may be increased growth of occult micro metastases.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this, animal studies have been undertaken which suggested that mediators released locally in the wound and systemically during the inflammatory phases of wound healing promote the growth, invasion and metastatic potential of human melanoma and other malignant tumour xenografts (Bogden et al, 1997;Hofer et al, 1998). There is also evidence from our laboratory that melanoma invasion in a model of human reconstructed skin requires the presence of host skin cells (namely fibroblasts and keratinocytes) that express characteristics of 'wounded' skin (Eves et al, 2000;Eves et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration of cancer progression after surgery is evident in clinical settings and in experimental animals (Kodama et al, 1992;Bogden et al, 1997). This means that tissue injury accompanying surgical treatment may offer the specific environment which influences dissemination of cancer cells, if residual cancer cells are present in the resected margin or in the wound fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Since surgical resection of carcinomas often results in acceleration of cancer progression and dissemination (Kodama et al, 1992;Bogden et al, 1997), we considered that HGF might influence the invasive potential of pancreatic cancers after surgery. To address this issue, SUIT-2 cells were cultured in the Matrigel invasion chamber in the presence of ascites obtained from a surgical patient with pancreatic cancer ( Figure 6A).…”
Section: Nk4 Inhibits Cancer Invasion Stimulated By Ascitic Fluid Aftmentioning
confidence: 99%